Heat transfer growth of sonochemically synthesized novel mixed metal oxide ZnO+Al2O3+TiO2/DW based ternary hybrid nanofluids in a square flow conduit. (July 2021) - Ahmed, Waqar; Kazi, S.N.; Chowdhury, Z.Z.; Johan, Mohd Rafie Bin; Mehmood, Shahid; Soudagar, Manzoore Elahi M.; Mujtaba, M.A.; Gul, M.; Ahmad, Muhammad Shakeel
Abstract: In the current investigation, the heat transfer development with the turbulent flow of novel metal oxide-based ternary composite nanofluids of ZnO + Al2 O3 +TiO2 /DW at varying wt.% concentrations (0.025, 0.05, 0.075, and 0.1) in a square heat exchanger below constant heat flux conditions was discussed. The new ternary composite nanofluids were synthesized by using the sonochemical technique. The ZnO + Al2 O3 +TiO2 /DW based ternary composite nanofluids with their respective wt. % reveals an enhancement in effective thermal conductivity and heat transfer coefficient local and average with Reynolds numbers varying from 4550 to 20, 367. The extreme growth in overall effective thermal conductivity was noticed up to 1.149 W/m-K at 0.1 wt% for ternary hybrid composite nanofluids at a maximum temperature 45 °C. Similarly, at 0.075 wt%, 0.05 wt%, and 0.025 wt% the overall effective thermal conductivity was recorded 1.118 W/m-K, 1.091 W/m-K, and 1.079 W/m-K correspondingly, which is greater than that of base fluid (DW), with improved thermo-physical characteristics for novel ZnO + Al2 O3 +TiO2 /DW ternary hybrid composite nanofluids. Also, it shows an improvement in local and average heat transfer with a maximum growth of 0.1 wt %. The maximum heat transfer was observed for ZnO + Al2 O3 +TiO2 /DW based Ternary hybrid composite nanofluids at 0.1 wt % concentrations, up to 900–5700 W/m 2 K, which is 89% higher than distilled water. While, an enhancement of 900–3870 W/m 2 K, 900–3350 W/m 2 K, 900–2750 W/m 2 K were observed for the other three wt. % 0.075, 0.05 and 0.025, respectively. The study revealed that the metal oxide based ternary hybrid composites nanofluids are suitable for nano coolant applications due to improved thermophysical characteristics and also it is applicable for energy management in industrial applications. Highlights: The sonochemical synthesis route for ZnO nanoparticles has discussed. Preparation of Ternary composite nanofluids (varying wt.%) by using high probe sonication. The study of different thermophysical and hydrodynamic characteristics of novel Ternary hybrid nanofluids. Analysis of heat transfer growth in the square channel by using ZnO + Al2 O3 +TiO2 /DW Ternary composite nanofluids.